Preservation Of Islamic Educational Values Amid The Transformation Of The Batamat Al-Qur’an Tradition Among The Banjar Community - Indah Rahmawati; Nuril Khasyi'in (Afkaruna: International Journal of Islamic Studies (AIJIS), 2026)
This study aims to analyze the preservation of Islamic educational values within the batamat Al-Qur’an tradition of the Banjar community amid its transformation in form and context. The tradition, once conducted privately at home, has evolved into an institutional activity in non-formal and formal educational settings. This research employs a qualitative descriptive method through interviews, observations, and documentation involving Qur’an teacher, head of the institution, and community figure as informants. Data were analyzed using the Miles and Huberman model with source and method triangulation. The results show that despite the changes in practice, Islamic educational values such as respect for teachers, reverence for the Qur’an, social bonding, charity, and habitual Qur’an recitation remain preserved. These values are reflected in three main dimensions: ʿibâdah (worship), akhlâq (morality), and tawhîd (faith). The batamat Al-Qur’an tradition thus serves as a medium for internalizing Islamic educational values that adapt to contemporary developments.